Review of the Knowledge on Selective Serotonin Reuptake Inhibitors (SSRIs) for Depression Management by Residents and Concurrent Physicians of the Medical Clinic of 5 Hospitals in CABA - Barbosa Eyler, Gonzalo E.; Ravizza, Sergio D. (Revista del Hospital Italiano de Buenos Aires, 2023)
Introduction: Depression is an increasingly common disorder around the world. General practitioners are the most frequently consulted health professionals by depressed patients. More than 70% of all depressed patients receive treatment by general practitioners and not by psychiatric specialists. According to studies conducted in Buenos Aires, more than 25% of all patients admitted to the Clinical Services in public hospitals present depression. These patients are usually under the care and follow-up of clinical trainee physicians, residents, or interns. This study aimed to analyze the knowledge about selective serotonin reuptake inhibitors (SSRIs) of clinical trainee residents and interns in five hospitals in the Ciudad Autónoma de Buenos Aires (CABA) and to describe their treatment of a depressive patient. Material and methods: We conducted a descriptive cross-sectional study with a non-probabilistic sampling. We used a semi-structured questionnaire arranged into two sections as a measuring tool. One, with demographic data to describe the sample. The other, with 15 items, explores respondents’ knowledge of SSRIs and the treatment of depression. Four experts reviewed the questionnaire, which was anonymous. We applied it to 59 clinical medical trainees, residents, and interns from five CABA hospitals who volunteered to participate during August-September 2022. Results: Most clinical trainees do not treat depressive conditions and, when confronted with a depressed patient, request an assessment by a Mental Health specialist. Only 6.8% medicate the patient with an antidepressant. More than 75% of the sample reported remembering their knowledge of SSRIs from the Pharmacology course and 13.6% from the Psychiatry course at the School of Medicine. Conclusion: There is a deficient knowledge about SSRIs in trainee residents and interns of Clínica Médica. We believe it is necessary to reinforce training on depression and management of antidepressants during residency/internship practice in Clínica Médica.